Cardiovascular disease determinants: Burden and knowledge among women in a rural community of Delhi - Jitendra K. Meena,; Anjana Verma,; Bratati Banerjee,; Gopal Krishna Ingle, (Universiti Kebangsaan Malaysia, 2015)
Background: Cardiovascular diseases (CVDs) are becoming major health burden in developing countries such as India. Rural women are reported to have high CVD-related mortality rates and are less likely to receive appropriate treatment. Objective: To assess knowledge, practices, and burden of CVD-related risk factors among women in a rural area of Delhi. Materials and Methods: A cross-sectional study was conducted at Pooth Khurd village, a rural pocket situated in northwest district of Delhi through house-to-house survey by two investigators. A total of 100 women above 18 years of age and resident of the village were included in the study using systematic random sampling technique. A pretested interview schedule, containing items to assess knowledge and practices regarding CVDs and risk factors based on various validated tools, was used. Fischer’s exact and Pearson’s correlation tests were applied; tests were two sided with p-value below 0.05 considered significant. Results: Poor CVD knowledge was seen among study participants with less than half of subjects identifying family history (24%), tobacco and alcohol intake (48%, 47%), and so forth as risk factors for CVDs. High burden of risk factors, such as high salt intake (35%), inadequate physical activity (77%), and raised blood sugar (5%), and poor health-seeking behavior were observed. Conclusion: This study reflects poor knowledge and relatively high burden of CVD risk factors among rural women. Poor knowledge is predictive of high CVD risk in community settings.